The Impact of Using Interactive Digital Media on Students' Mathematical Reasoning Abilities in Derivative Material - Asdar Dollo; Henra Ahmad; Abdul Rahman; Risfandi Ibrahim (Universitas Islam Ahmad Dahlan (UIAD), 2025)
Mathematical reasoning ability is one of the essential competencies that need to be developed in 21st-century mathematics learning. However, the results of preliminary studies indicate that this ability is still in the moderate category, with the main weakness in the aspect of mathematical manipulation. This study aims to analyze the impact of the use of interactive digital media on improving students' mathematical reasoning abilities, as well as identifying the most affected indicators. The study used a pre-test - post-test design with a population of six sixth-semester students of the Mathematics Education Study Program, Universitas Muhammadiyah Pare-pare. The research instrument was a descriptive test designed to measure three indicators of mathematical reasoning, namely proposing conjectures, presenting mathematical statements, and performing mathematical manipulation. The results of the descriptive analysis showed an increase in the average score from 58.33 (medium category) in the pre-test to 80.09 (high category) in the post-test, with a normalized gain of 0.52 which is in the medium category. The decrease in the standard deviation from 7.86 to 5.67 indicates that student achievement became more homogeneous after the treatment. Analysis per indicator showed that the largest increase occurred in the indicator of proposing conjectures (27.78 points), followed by presenting mathematical statements (23.61 points), while the indicator of performing mathematical manipulation experienced the lowest increase (13.89 points). These findings confirm that interactive digital media is more effective in strengthening high-level mathematical reasoning skills based on visual and conceptual representations, while procedural skills still require additional manual practice support. Overall, this study concludes that the integration of interactive digital media has the potential to be an effective pedagogical strategy for improving students' mathematical reasoning abilities, while reducing individual variation in achievement. The practical implication of this study is the need for a balanced learning design, combining the use of interactive digital media and conventional practice strategies to comprehensively strengthen all aspects of mathematical reasoning